Impact of digital marketing on customer loyalty among Universiti Malaysia Kelantan Pengkalan Chepa students - Muhammad Adam Iskandar Ab. Wahab; Nur Adiha Mohamad Yunus; Nurul Syahidah Ahmad Kusairi; Siew Kai Ern (2024)
The digital marketing landscape has transformed brand engagement, enabling businesses to showcase and compare products online. This study focuses on the impact of digital marketing, including social media marketing (SMM), search engine optimization (SEO), content marketing (CM), and influencer marketing (IM), on customer loyalty among Universiti Malaysia Kelantan, Pengkalan Chepa students. Despite the evolution of digital marketing, there's a research gap in understanding how these strategies collectively influence customer loyalty. The study, with a quantitative design and 256 respondents, reveals positive relationships between social media marketing, SEO, content marketing, influencer marketing, and customer loyalty. Influencer marketing emerges as the most influential factor among UMK students. This research highlights the need for further exploration of keywords such as digital marketing, customer loyalty, digital marketing strategies, social media, and digital content marketing. The study provides valuable insights and identifies trends for future investigations.